2020
DOI: 10.18203/2394-6040.ijcmph20200460
|View full text |Cite
|
Sign up to set email alerts
|

Study of socio-demographic and treatment profile and other epidemiological correlates of clients attending revised national tuberculosis control programme clinic in a tertiary hospital of West Bengal, India

Abstract: Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis bacteria spread by droplet infection.According to global TB report 2017, there were approximately 28 lakhs cases of TB in India accounting a quarter of the world TB cases. Today, it is the fastest-expanding and the largest program in the world in terms of patients initiated on treatment and the second largest in terms of population coverage. The objective of this study is to assess the socio-demographic profile of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…which is quite higher than 16.7% reported by Karanjekar et al and lower than 41% reported by Kundu et al7,14 Total success rate of RNTCP in studied area for the studied period was 88.49% in this study which is almost equal to data (88.0%) shown byAgarwal et al …”
contrasting
confidence: 60%
“…which is quite higher than 16.7% reported by Karanjekar et al and lower than 41% reported by Kundu et al7,14 Total success rate of RNTCP in studied area for the studied period was 88.49% in this study which is almost equal to data (88.0%) shown byAgarwal et al …”
contrasting
confidence: 60%
“…A study by Kundu et al . [ 10 ] in an adjoining district of West Bengal also observed that 14% of TB patients had a history of TB contacts.…”
Section: Discussionmentioning
confidence: 98%
“…Quitting smoking and avoiding exposure to passive tobacco smoke are essential factors in TB control. [ 9 10 ] Obore et al . [ 11 ] observed a two-fold rise in the risk from exposure to second-hand tobacco smoke (RR = 2.15, 95%CI 1.419–3.242), and tobacco smoking doubled the risk of contracting TB (RR = 2.67, 95%CI 2.017–3.527).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations